Perbaikan Fasilitas Dan Sosialisasi Sadar Wisata Dalam Pengembangan Objek Wisata Pantai Bohay Di Desa Binor Kecamatan Paiton Kabupaten Probolinggo - Mubaroq, Husni; Devi, Nourma Ulva Kumala; Wahyuningsasi, Evi Wulandari; Ikhsan, Moh. Taufik Khoiril (Abdi Panca Marga, 2023)
Tourism development is important as a source of income for the government and the community, with community tourism development can open up business opportunities that improve welfare. This study aims to analyze the efforts of the local government in developing the Bohay Beach Tourism Object in Paiton District, Probolinggo Regency. Empirically this natural tourist attraction has not received attention from the Probolinggo Regency government. In theory, this research uses development theory, namely a theory consisting of attractions, accessibility, public facilities, and inhibiting and supporting factors. This research method is carried out using qualitative research methods, data collection techniques are carried out by observation, interviews, and documentation. The results of the study indicate that there is no government effort in the development carried out by the Probolinggo Regency government of the Bohay Beach tourist attraction and the obstacles to this research indicate that the local community does not want this tourist attraction to be managed by the government because this will reduce the income for the local community and there is no government policy that used as a legal basis for developing tourism objects. The conclusion of this study shows that the Probolinggo Regency government has not carried out a strategy for developing Bohay Beach tourism objects.